Παράγοντες που επηρεάζουν την οικονομική εξέλιξη των συνταξιοδοτικών συστημάτων - Κυριάκη Δ. Ι. (SPOUDAI Journal of Economics and Business, 1999)
The financial evolution of pension funds is dependent on some factors, as demography, investments, actuarial technical e.t.c. In this article, we analyze the above factors, but we focus essentially on the actuarial method of calculation the present value of the insurance benefits. In order to calculate precisely the present value of the insurance benefits, we develop formulae which include: a. the way of calculating the benefits as it is refered to the rules of pension fund, b. the limitations which are set by the rules of the pension fund in determing the amount of the benefit, c. the conditions of granting of the benefit, d. the favourable articles of the rules of the pension fund, for the administration of greater benefits than those which correspond to the exact years of insurance, e. the development in the saleries of the insured and, f. the probabilities of the withdrawal of the insured from the pension fund due to the old age, disability, death and other causes. Moreover those formulae: a. can be used to illustrate the annual effect of insurance on the calculations of the present values of the benefits, b. are broken down into Past Service Benefits and Future Service Benefits and, c. can be expressed through the commutation functions.